Abnormal right atrial performance in repaired tetralogy of Fallot: A CMR feature tracking analysis. (1st December 2017) - Kutty, Shelby; Shang, Quanliang; Joseph, Navya; Kowallick, Johannes T.; Schuster, Andreas; Steinmetz, Michael; Danford, David A.; Beerbaum, Phillip; Sarikouch, Samir
Abstract: Background: We hypothesized that right atrial (RA) performance is abnormal in repaired tetralogy of Fallot (TOF). Methods: TOF patients were prospectively enrolled for cardiovascular magnetic resonance (CMR), echocardiography and exercise stress following a standardized 14-center protocol. Peak RA longitudinal strain (RALS) and right ventricular longitudinal strain (RVLS) were measured using CMR feature tracking (FT) and correlated to RA and RV end diastolic volumes (EDVi) and ejection fraction (EF). Results: The cohort had 311 subjects: 171 TOF (94 male, age 18.2 ± 8 years) and 140 healthy controls (69 male, 16.4 ± 11 years). RAEDVi, RALS, RVEDVi, RVLS, RAEF, and RVEF in TOF were 60.8 ± 17.1 ml/m 2, 13.6 ± 5.7%, 120.3 ± 30.3 ml/m 2, 12.3 ± 4.2%, 32.5 ± 9.9% and 51.2 ± 8.4% and differed from respective indices in controls: 51.7 ± 15.7 ml/m 2, 27 ± 10.1%, 74 ± 19.0 ml/m 2, 18.5 ± 5.3%, 54 ± 8% and 62.5 ± 5.5% (p < 0.001). RAEDVi and RALS correlated with RVLS (p = 0.004, < 0.001, r = 0.2, 0.3). RAEDVi was higher in older TOF, while RALS did not increase with age. RAEDVi but not RALS correlated with RV systolic pressure(r = 0.2, 0). Neither RAEDVi nor RALS was associated with tricuspid regurgitation grade or peak oxygen uptake (r = 0.1, 0). Positive correlation was observed for RVEDVi with RAEDVi (p = 0.035, r = 0.2) and a trend toward negative correlation with RALS (p = 0.09, r = 0.1). Conclusion: RALS, RAEDVi and RAEF are abnormal in TOF. Reduced RALS indicates decreased RA reservoir function. Because they correlate with other functional RV indices, these abnormalities may represent RA diastolic burden from chronic RV dysfunction in TOF. The young cohort age might explain the absence of RALS correlation to tricuspid regurgitation and peak oxygen uptake.